A smartphone application to reduce problematic drinking: a feasibility trial - Christian Aljoscha Lukas; Jens Blechert; Matthias Berking (Pilot and Feasibility Studies, 2024)
Abstract Background Problematic drinking is common among college students and associated with various somatic and mental health problems. Given significant evidence for the efficacy of smartphone-based interventions and the frequent use of smartphones among college students, it can be assumed that such interventions have great potential to facilitate access to evidence-based interventions for students suffering from problematic drinking. Thus, we developed a brief intervention that combined a counseling session with an app that utilizes approach-avoidance modification training to reduce alcohol consumption. Methods To test the feasibility and explore the potential efficacy of the intervention, we conducted a before-after single-arm study with N = 11 participants reportedly engaging in problematic drinking, who were instructed to practice with the app for 14 days. Feasibility was assessed with the System Usability Scale (SUS). Outcomes included the reduction of self-reported problematic drinking behavior, dysfunctional attitudes about alcohol, and craving, as well as implicit associations between alcohol and self during the training period. Additionally, self-reported problematic drinking behavior was assessed at a 4-week follow-up. Results On average, participants rated app usability on the SUS (possible range: 0 to 100) with M = 84.32 (SD = 6.53). With regard to efficacy, participants reported a significant reduction of problematic drinking behavior (d pre vs. post  = 0.91) which was sustained at follow-up (d follow-up vs. baseline  = 1.07). Additionally, participants reported a significant reduction of dysfunctional attitudes about alcohol (d pre vs. post  = 1.48). Results revealed no significant changes in craving nor in implicit associations regarding alcohol. Conclusions Findings from this feasibility study provide preliminary evidence that smartphone-based interventions might help reduce problematic drinking in college students. Further research needs to replicate these findings with larger samples in randomized controlled trials. Trial registration DRKS00014675 (retrospectively registered).